8(1-4n)-3(4+7n)=27

Simple and best practice solution for 8(1-4n)-3(4+7n)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(1-4n)-3(4+7n)=27 equation:


Simplifying
8(1 + -4n) + -3(4 + 7n) = 27
(1 * 8 + -4n * 8) + -3(4 + 7n) = 27
(8 + -32n) + -3(4 + 7n) = 27
8 + -32n + (4 * -3 + 7n * -3) = 27
8 + -32n + (-12 + -21n) = 27

Reorder the terms:
8 + -12 + -32n + -21n = 27

Combine like terms: 8 + -12 = -4
-4 + -32n + -21n = 27

Combine like terms: -32n + -21n = -53n
-4 + -53n = 27

Solving
-4 + -53n = 27

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -53n = 27 + 4

Combine like terms: -4 + 4 = 0
0 + -53n = 27 + 4
-53n = 27 + 4

Combine like terms: 27 + 4 = 31
-53n = 31

Divide each side by '-53'.
n = -0.5849056604

Simplifying
n = -0.5849056604

See similar equations:

| 3/5(15t-2)= | | (i)(1+8i)= | | 3x+21=10x | | 3(x-2)=30 | | 15+6k=7+7k | | 5(10x-10)=-5(4x+4) | | -40-8k=-8(1+5k) | | 70-q-q-2q=90 | | -3(.25)+.6=7+x+y | | 21-2(5r+3)=-6r+1-2r | | 25=3u-4 | | 1y=5+2x | | 12=-4+4x | | x(6)+x(7)=52 | | 4.4+6.2=8.8s-1.8 | | -5v+2v=-8+14 | | C=0.41+0.26(z-1) | | 5(4x-2)=33 | | 3.93-15.3g=4.53-15g | | -(n-6)-8=-(1+n) | | -5u^2+24u=-5 | | 60x+30(60)=50x+50(60) | | 19+20h=-134(-5h-8) | | -2-11x=-35 | | 5x-14-7x+4=2-8x-8+2x | | .6y-3x=x+y+7 | | -(n-6)-8=(1+n) | | -3(-f-1)=3f+3 | | -2(y+7)=16 | | 8=-4(3-10p)+7p | | 27-6=17x-26 | | X-8=-36+5x |

Equations solver categories